Search for leptophobic Z′ bosons decaying into four-lepton final states in proton–proton collisions at s=8TeV - Khachatryan, Vardan; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Md. Ali, Mohd. Adli (Elsevier B.V., 2017)
A search for heavy narrow resonances decaying into four-lepton final states has been performed using proton–proton collision data at √s = 8 TeV collected by the CMS experiment, corresponding to an integrated luminosity of 19.7 fb−1. No excess of events over the standard model background expectation is observed. Upper limits for a benchmark model on the product of cross section and branching fraction for the production of these heavy narrow resonances are presented. The limit excludes leptophobic Z bosons with masses below 2.5 TeV within the benchmark model. This is the first result to constrain a leptophobic Z resonance in the four-lepton channel